2020
DOI: 10.1002/ctpp.201900081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the single nanosecond pulsed surface dielectric barrier plasma actuator: Geometric and electric effects

Abstract: The influence of the electrode length and the voltage pulses on the discharge characteristics of the surface dielectric barrier discharge actuators were investigated numerically by using the plasma kinetic model. The governing equations including the coupled continuity plasma discharge equation, drift‐diffusion equation, electron energy equation, Poisson's equation, and Navier–Stokes equation were solved in quiescent air at atmospheric pressure. The results show that the shorter pulse rising time results in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The effect of pulse repetition frequency on the residual surface charge of NS-SDBD was investigated by Peng et al [20]. The influence of the rise time on the discharge characteristics of NS-SDBD was investigated by Xu et al [21], and the results revealed that the shorter the rise time, the greater the discharge intensity and discharge area.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pulse repetition frequency on the residual surface charge of NS-SDBD was investigated by Peng et al [20]. The influence of the rise time on the discharge characteristics of NS-SDBD was investigated by Xu et al [21], and the results revealed that the shorter the rise time, the greater the discharge intensity and discharge area.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the computational cost of the fluid-based model is relatively lower, which is potentially realizable for three-dimensional modelling, and it is fully coupled with the Navier-Stokes equations, compared with a physics-based model that considers a kinetics scheme, limitations still appear because it is highly parametric dependent and the evolution of detailed species during the discharge process is neglected. Xu [23] proposed a kinetics scheme of seven species and nine reactions and the effects of configurations of the exposed surface of the driven electrode [24], geometry and waveform of voltages [25] on NS-DBD on a flat surface were investigated. The results show that the reduced electric field of the serrated electrode is the greatest as well as the strength of the compression wave and its propagation speed, while results of the semicircular electrode are the weakest.…”
Section: Introductionmentioning
confidence: 99%